Adjustment of Membership Functions, Generation and Reduction of Fuzzy Rule Base From Numerical Data - Ketata, Raouf; Bellaaj, Hatem; Chtourou, Mohamed; Amer, Mohamed Ben (Malaysian Journal of Computer Science, 2017)
In this paper we introduce a new approach for adjustment of membership functions, generation, and reduction of fuzzy rule base from data in the same time. The proposed approach consists of five steps: First, generate fuzzy rules from data using Mendel & Wang Method introduced in [1]. Second, calculate the degree of similarity between rules. Third, measure the distance between the numerical values which induces similar rules. Four, if the distance is greater than base value then merge membership functions. Finally, regenerate rules from data with new fuzzy sets. This approach is applied to truck backer-upper control and Liver trauma diagnostic. A comparative study with a simple Mendel Wang method shows the advantages of the developed approach.